Hubungan Pengetahuan Gizi, Kecukupan Energi dan Ketersediaan Pangan dengan Status Gizi Santri di Pesantren Darul Quro Karawang - Namyra, Laras; Andriani, Eka; Elvandari, Milliyantri (Universitas Pahlawan Tuanku Tambusai, 2025)
The provision of food in institutions is carried out to meet the nutritional needs of students, and the food provided in Islamic boarding schools has a major contribution to nutritional intake. Factors related to nutritional problems in adolescents include many things such as nutritional knowledge, food consumption and food availability. The aim of this research is to determine the relationship between nutritional knowledge, energy adequacy and food availability and the nutritional status of the students. This research uses a mixed research design or mixed method with a cross sectional approach, namely by measuring variables at one time with the aim of finding out the relationship between variables. The results of the research show that students at the Darul Quro Karawang Islamic boarding school have normal nutritional status, have good nutritional knowledge, and experience moderate energy deficit and food availability and have high food security with a score of 0. The results of the analysis using the Spearman test, it can be seen that there is a relationship between nutritional knowledge and energy adequacy with the nutritional status of students at Darul Quro Karawang Islamic Boarding School and food availability at Islamic boarding schools that have high food security.